Implementation of IoT-based Appropriate Technology in the Rabbit Farming Group in Sumberejo Village - Dura, Justita; Hadi, Abd; Sidi, Agus Purnomo (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service activity aims to improve the productivity and welfare of rabbit breeders through the implementation of innovative Internet of Things (IoT)-based cages. This innovation includes automatic monitoring of cage temperature and humidity and an automated roll system for waste disposal. Method: The program is implemented using extension, training, practice, and equipment handover methods at the